Estimating the Intrinsic Value of an Integrated Financial Management System: A Live Case - Gentry, J.; Reilly, F.; Evans, John (RMIT University, 2012)
The primary objective of this manuscript is to create a dynamic learning experience for students and an exciting teaching experience for professors. To achieve this goal we develop an Integrated Financial Management System [IFMS] that simulates a company’s (1) financial forecast and (2) estimates of the enterprise and equity value. The inputs for the simulation are based on Live Case information that is provided by experienced financial executives. In essence, IFMS provides students a user friendly model that creates a financial forecast and estimates the intrinsic value of a company and its stock value. Live Cases motivate students to become deeply committed to an experimental learning environment. Students become actively involved in using financial information provided by a company’s financial staff members that greatly enhance their financial forecast. Our experience shows Live Cases cause students to research other data sources to enhance the financial forecast. Likewise it is crucial for students to question the strategic macro-economic assumptions that underlie the entire valuation process. The IFMS simulations highlight the dynamic interactions among operating, investment and financial strategies in forecasting a firm’s value.